Ocular dimensions of young Malays in Malaysia(Dimensi Okular Remaja Melayu di Malaysia) - Mohd Ali, Bariah; Abdul Rahim, Muhammad Afzam Shah; Mohammed, Zainora; Mohidin, Norhani (Penerbit Universiti Kebangsaan Malaysia, 2011)
It is well documented that ocular dimensions vary with race. However few data on the Malay population was available in the literature. The purpose of this study is to establish normal values of ocular dimensions among one sample of young Malay population in Malaysia. A total of 584 healthy subjects from around Kuala Lumpur volunteered for the study. Measurements include corneal curvature and central thickness, corneal eccentricity value (e), horizontal and vertical visible iris diameter, pupil size and size of palpebral aperture. Subjects were divided into 3 different groups and were age and gender matched: Group 1 (7-12 years old, n = 188), Group 2 (13 to 18 years old, n = 196) and Group 3 (19 to 24 years old, n = 200). Parameters were measured using corneal topographer (CTK 922 from Haag Streit, Germany), ultrasonic pachometer (Corneo-Gage Plus 2 from Sonogage Incorporated) and auto refractometer (Auto- Ref R1 from Canon, Japan). Ocular dimensions measured found to be smaller and different from other ethnics groups from around the world. Significant differences in all measurements were also observed with age increment (p <0.05). The results found from this study can be used as future reference for ocular dimensions in young Malaysians.